Shipment policy optimisation in a return supply chain for online retailers via stochastic discrete event simulation. (2016) - Li, Haobin; Pedrielli, Giulia
Limiting the costs for return of products is a key competing factor for online retailers. In fact, free returns are considered an important performance to the customer. However, to guarantee free returns, the company has to precisely estimate the costs implied in the return supply chain. In this paper, we specifically look at the problem of international online retailers that have to manage the shipment of return products between different countries. In this scope, we first formalise the return process and we propose a two-parameters strategy to manage the shipment of returned products across countries. In order to solve the problem, we propose to use simulation-optimisation, resulting in a general solution approach not limited by stringent assumptions.